AmrZ and FleQ Co-regulate Cellulose Production in Pseudomonas syringae pv. Tomato DC3000 - Pérez-Mendoza, Daniel; Felipe, Antonia; Ferreiro, María Dolores; Sanjuán, Juan; Gallegos, María Trinidad (Frontiers in Microbiology, 2019)
Pseudomonas syringae pv. tomato DC3000 carries the wssABCDEFGHI operon for the synthesis of acetylated cellulose, whose production is stimulated by increasing the intracellular levels of the second messenger c-di-GMP. This enhances air-liquid biofilm formation and generates a wrinkly colony morphotype in solid media. In the present study we show that cellulose production is a complex process regulated at multiple levels and involving different players in this bacterium. Using different in vitro approaches, including Electrophoretic Mobility Shift Assay (EMSA) and footprint analysis, we demonstrated the interrelated role of two transcriptional regulators, AmrZ and FleQ, over cellulose production in Pto DC3000 and the influence of c-di-GMP in this process. Under physiological c-di-GMP levels, both regulators bind directly to an adjacent region at the wss promoter inhibiting its expression. However, just FleQ responds to c-di-GMP releasing from its wss operator site and converting from a repressor to an activator of cellulose production. The additive effect of the double amrZ/fleQ mutation on the expression of wss, together with the fact that they are not cross-regulated at transcriptional level, suggest that FleQ and AmrZ behave as independent regulators, unlike it has been described in other Pseudomonas species. Furthermore, this dual co-regulation exerted by AmrZ and FleQ is not limited to cellulose production, but also affects other important phenotypes in Pto DC3000, like motility and virulence.